Super-resolution imaging of lysosomes with a nitroso-caged rhodamine. Issue 23 (2nd February 2018) - He, Haihong; Ye, Zhiwei; Zheng, Ying; Xu, Xiu; Guo, Chunlei; Xiao, Yi; Yang, Wei; Qian, Xuhong; Yang, Youjun
Abstract : N, N ′-Dinitroso caged rhodamine are potentially suitable for photo-activated localization microscopy (PALM) of lysosomes. Abstract : Caged-fluorophores are potentially suitable for photo-activated localization microscopy (PALM) for super-resolution imaging. N -Nitroso is a simple and robust photo-cage with biocompatible nitric oxide as the only byproduct upon photolysis. We herein reported a novel PALM probe (NOR535 ) for super-resolution imaging of lysosomes with high localization precision.